2023
DOI: 10.3390/plants12040832
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Sodium Nitroprusside on Photosynthetic Performance of Sorghum bicolor L. under Salt Stress

Abstract: In this study, the impacts of the foliar application of different sodium nitroprusside (SNP, as a donor of nitric oxide) concentrations (0–300 µM) on two sorghum varieties (Sorghum bicolor L. Albanus and Sorghum bicolor L. Shamal) under salt stress (150 mM NaCl) were investigated. The data revealed that salinity leads to an increase in oxidative stress markers and damage of the membrane integrity, accompanied by a decrease in the chlorophyll content, the open photosystem II (PSII) centers, and the performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 103 publications
1
11
0
Order By: Relevance
“…This increase in the photochemical quenching (qP) was observed to a smaller extent in maize than in sorghum ( Figure 3 ). The influence of SNP on the open PSII centers, alongside the increase in their efficiency, could also be a reason for the influence on the stress tolerance of the plants after exogenous treatment with SNP, a donor of NO [ 12 ]. At the same time, values for the rate constants ( k 1 and k 2 ) of the decay of flash-induced variable fluorescence in both studied plant species were influenced in different ways ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This increase in the photochemical quenching (qP) was observed to a smaller extent in maize than in sorghum ( Figure 3 ). The influence of SNP on the open PSII centers, alongside the increase in their efficiency, could also be a reason for the influence on the stress tolerance of the plants after exogenous treatment with SNP, a donor of NO [ 12 ]. At the same time, values for the rate constants ( k 1 and k 2 ) of the decay of flash-induced variable fluorescence in both studied plant species were influenced in different ways ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The endogenous production of NO takes place in different organelles like peroxisomes, mitochondria and chloroplasts [ 1 , 3 , 11 ]. Recent studies have shown that the endogenous content of NO in plants under physiological conditions is variety-specific [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of the pigments in leaves were determined as described in [74]. The amounts of Chl a, Chl b, and Car were measured using a Specord 210 PLUS spectrophotometer (Edition 2010, Analytik-Jena AG, Jena, Germany), and the pigment content was calculated using Lichtenthaler's equations [73].…”
Section: Pigment Content In Leavesmentioning
confidence: 99%
“…High salt concentration induces damage in proteins, lipids, and nucleic acid, leading to increased ROS [ 12 ]. Previous studies revealed increased hydrogen peroxide (H 2 O 2 ) in wheat and sorghum, as the enhancement of H 2 O 2 strongly depends on the tolerance of plant genotypes [ 11 , 14 ]. Activating the antioxidant enzymes and synthesis of protective components are very important for the survival of plants under salt stress [ 11 , 15 ].…”
Section: Salt Stressmentioning
confidence: 99%